A CONSCIENTIZAÇÃO COMO FATOR DE DESENVOLVIMENTO DA ATIVIDADE TURÍSTICA - Milene Torelli Lapenta (Universidade do Oeste Paulista, 2007)
This article aims to demonstrate the importance to elaborate projects that objective to make the community and tourists conscious of the importance in developing the Tourism and the benefits that this activity may provide. So, researches were made with young college students to register the enterviewed level of consciousness and knowledge in relation to the tourism development in some place. The first part of the research diagnoses, by making questions, the existence or non-existence of the knowledge mans, among young high school students, about the benefits of turism. The result was most people don't have knowledge about the tourism activity yet, development of the towns with tourism potency.